2009
DOI: 10.1038/sj.bjc.6605331
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Coxsackie and adenovirus receptor downregulates α-catenin expression

Abstract: BACKGROUND: The Coxsackie and adenovirus receptor (CAR) has been shown to inhibit cancer cell proliferation, migration, and invasion. The underlying mechanisms, however, are poorly understood. METHODS: The differential gene expression in the human colon cancer cell line DLD1 on RNAi-mediated functional CAR knockdown was analysed using oligo-array technology. Expression of a-catenin was determined by quantitative RT-PCR and western blotting. Proliferation, migration, and invasion after CAR knockdown were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
0
13
1
Order By: Relevance
“…Stecker et al . reported that knockdown of CXADR inhibits α-catenin expression13, but we could not obtain the same results in this study (data not shown). Thus, our results suggest that CXADR could not play a critical role in tumorigenesis.…”
Section: Discussioncontrasting
confidence: 79%
“…Stecker et al . reported that knockdown of CXADR inhibits α-catenin expression13, but we could not obtain the same results in this study (data not shown). Thus, our results suggest that CXADR could not play a critical role in tumorigenesis.…”
Section: Discussioncontrasting
confidence: 79%
“…Since cell surface E-cadherin associates with the transcription factor β-catenin, the internalization of E-cadherin by CAR may dissociate the E-cadherin-β-catenin complex allowing for β-catenin translocation into the nucleus resulting in enhanced cell proliferation. In line with this hypothesis, knockdown of CAR has been reported to downregulate α-catenin in a human colon cancer cell line, suggesting that CAR may regulate adherens junction proteins to control cell proliferation [161]. …”
Section: Jam Family Members In Leukocyte Recruitment and Mucosal Inflmentioning
confidence: 97%
“…The establishment of cell lines was confirmed by immunofluorescent (IF) staining, which was performed as described previously with slight modification [ 32 ]. Briefly, two samples were rinsed and fixed with precooled ethanol (10 min at −40 °C).…”
Section: Methodsmentioning
confidence: 99%